PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS YANG DIMODERASI OLEH KEPUASAN KONSUMEN PADA HUNTER GYM DI KOTA PEKANBARU - Lestari, Tri Puji Endang; Jushermi, Jushermi; Noviasari, Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to determine the effect of Service Quality and Price on Customer Satisfaction and Customer Loyalty at Gym Hunter in Pekanbaru City. The object of this research is Gym Hunter fitness services. This research use Loyalty as endogenous variable and Satisfaction as moderation variable. While the exogenous variables in this study are Service Quality and Price. The population in this study is not known with certainty and the sample used in this study is 112 people. This study uses accidental sampling, ie anyone who meets the appropriate pene as a respondent. Data taken from the respondents using the core questionnaire. The analytical method used in this research is path analysis using SPSS (Statistical Package for Social Science) version 21. The results of this study indicate that Service Quality has a positive and significant impact on Consumer Satisfaction. Price has a positive and significant effect on Consumer Satisfaction. Service Quality has a positive and significant impact on Customer Loyalty. Price has positive and significant effect to Customer Loyalty. Consumer Satisfaction has a positive and significant impact on Customer Loyalty. The Service Quality has a positive and significant impact on Customer Loyalty through Custumer Satisfaction. Price has a positive and significant impact on Customer Loyalty through Customer Satisfaction. Consumer Satisfaction can be a moderating variable of Quality of Service and Price to Loyalty.Keywords: Service Quality, Price Customer Satisfaction, Loyalty